Relación entre el estado nutricional y el desarrollo psicomotriz en los niños preescolares del barrio Cañaro - Aldeán Aguirre, Gloria Lizeth (2014)
In order to evaluate the relationship between nutritional status and psychomotor development of preschool children of neighborhood Cañaro, parish Urdaneta, canton Saraguro, province of Loja, the study was quantitative-descriptive cross-prospective. For this study were evaluated 50 preschool children in the neighborhood in question. For this purpose we developed a data base sheet in Microsoft Excel 2010 to facilitate the tabulation of the data. Consent was obtained from parents of each child in order to conduct the study. The classification of nutritional status of children was performed using measurement techniques (weight and height) and the growth curves of the World Health Organization (WHO). Also applied to children Abbreviated Scale Development of Nelson Ortiz Pinilla which evaluating psychomotor development in the four areas. The results showed that the total Preschoolers 52% presented mild badnutrition. As psychomotor development 50% of all children in a state of alert. Of all children who presented nutritional alterations the psychomotor areas most affected were the fine motor with 38% and, 34% of children had alterations in the area of language, proving that nutritional status affects the psychomotor development. Parents of preschool children underwent surveys to feeding practices that have, and obtained the result that food practices are not adequate in 66% of the surveyed population. For availability of foodstuffs with this population were interviewed the key person in this community, the result of which was that food availability is extremely low.